Electrostatic Regulation of Na+ Coordination Chemistry for High-Performance All-Solid-State Sodium Batteries - Song, Penghui; Chen, Suli; Guo, Junhong; Wu, Junchen; Lu, Qiongqiong; Xie, Haijiao; Wang, Qingsong; Liu, Tianxi (Nano-Micro Letters, 2025)
Ion migration capability and interfacial chemistry of solid polymer electrolytes (SPEs) in all-solid-state sodium metal batteries (ASSMBs) are closely related to the Na+ coordination environment. Herein, an electrostatic engineering strategy is proposed to regulate the Na+ coordinated structure by employing a fluorinated metal–organic framework as an electron-rich model. Theoretical and experimental results revealed that the abundant electron-rich F sites can accelerate the disassociation of Na-salt through electrostatic attraction to release free Na+, while forcing anions into a Na+ coordination structure though electrostatic repulsion to weaken the Na+ coordination with polymer, thus promoting rapid Na+ transport. The optimized anion-rich weak solvation structure fosters a stable inorganic-dominated solid–electrolyte interphase, significantly enhancing the interfacial stability toward Na anode. Consequently, the Na/Na symmetric cell delivered stable Na plating/stripping over 2500 h at 0.1 mA cm−2. Impressively, the assembled ASSMBs demonstrated stable performance of over 2000 cycles even under high rate of 2 C with capacity retention nearly 100%, surpassing most reported ASSMBs using various solid-state electrolytes. This work provides a new avenue for regulating the Na+ coordination structure of SPEs by exploration of electrostatic effect engineering to achieve high-performance all-solid-state alkali metal batteries. Highlights: 1 An electrostatic engineering strategy is proposed to regulate the Na+ coordinated structure by employing a fluorinated metal–organic framework as an electron-rich model. 2 The abundant electron-rich F sites can accelerate Na-salt disassociation while forcing anions into Na+ coordination structure though electrostatic effect to weaken the Na–O coordination, thus promoting rapid Na+ transport. 3 Anion-rich weak Na+ solvation structure is achieved and contributes to a highly stable inorganic-rich solid–electrolyte interphase, significantly enhances the interfacial stability toward Na anode. 4 Impressively, Na/Na symmetric cell delivered stable Na plating/stripping over 2500 h, and the assembled all-solid-state sodium metal batteries demonstrated stable performance of over 2000 cycles under high rate of 2 C with capacity retention nearly 100%.